The Effectiveness of Implementing the Socialization of Agricultural Quarantine Regulations in Gorontalo Province - Yasin Husain; Widya Kurniati Mohi; Sri Hantuti Paramata (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
This study aims to obtain an overview of the Implementation of the Socialization of Agricultural Quarantine Regulations in Gorontalo Province, the research method uses qualitative type. Data collection techniques were carried out through interviews with a number of informants and observations and recording secondary data related to the research problem. If viewed from the source approach shows that resources have not been effective in supporting the successful implementation of the socialization of agricultural quarantine regulations because there are still some who do not understand the rules at the time of socialization, whereas in the process approach shows the implementation of quarantine regulation socialization in accordance with the Act or regulations has been determined but has not been effective because there are still obstacles encountered in its implementation, namely that there are still many who do not understand the quarantine regulation. The target approach shows that Gorontalo Class II Agricultural Quarantine Center Achievement has not been effective, because it has not achieved the desired target, the results of the implementation of the socialization have not been fully assessed. There are still obstacles in the form of the lack of commitment of quarantine officers or human resources. So that the impact on the lack of application of services.